Hedonizmden Püritanizme: Eğitim Felsefesine İlişkin Bir Değerlendirme - Öztürk Fidan, İnci (Muş Alparslan Üniversitesi, 2017)
Pleasure which means to feel sensual or spiritual joy has historically been a philosophical investigation subject. In the beginning, the ancient age views focusing on the happiness of individuals were prominent, but along with the enlightenment philosophical thoughts focusing on the happiness of the whole society came to the forefront. On the other hand, people who quit their pleasures and seek their salvation in the orders of God, adopt Puritan work ethics through hardwork and accumulation of capital. Educational policies aim to balance between the efforts to enable individuals to be happy in their lives and the efforts to equip them with ethical principles to guide them during their lives. In this study, philosophical and theoretical discussions regarding hedonism and puritanism were presented. The results of the hedonism and puritanism for educational organizations were also discussed.

Bir şeyden duyusal ya da tinsel sevinç duyma anlamına gelen haz kavramı tarih boyunca felsefî bir araştırma konusu olmuştur. Önceleri tek bir bireyin mutluluğuna odaklanan antik çağ öğretileri ön planda iken aydınlanma çağı ile birlikte tüm toplumun mutluluğuna odaklanan akımlar öne çıkmıştır. Öte yandan hazlarından vazgeçen ve kurtuluşunu yaratıcısının buyruğunda gören insanlar, sıkı çalışma ve kazandığını biriktirme yoluyla Püritan çalışma etiği ilkelerini benimsemiştir. Eğitim politikaları ise okulda ve okul sonrasındaki yaşamlarında bireylerin mutluluğunu sağlama çabası ile onlara yaşamları boyunca rehberlik edecek etik ilkeleri kazandırma çabası arasındaki uyumu sağlamayı amaç edinmiştir. Bu çalışmada hedonizm ve püritanizm akımlarına ilişkin felsefî ve kuramsal tartışmalara yer verilmiştir. Ayrıca tartışma ve sonuç bölümünde hedonizm ve püritanizmin eğitim örgütleri açısından doğurgularına değinilmiştir.
From Hedonism to Puritanism: An Evaluation of the Philosophy of Education
anemon
Keywords: Hedonism; Puritanism; Work Ethics; Capitalism; Values Education; Hazcılık; Püritanizm; Çalışma Etiği; Kapitalizm; Değerler Eğitimi